2021
DOI: 10.1186/s13014-021-01933-z
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam CT-based dose accumulation and analysis of delivered dose to the dominant intraprostatic lesion in primary radiotherapy of prostate cancer

Abstract: Background Evaluation of delivered dose to the dominant intraprostatic lesion (DIL) for moderately hypofractionated radiotherapy of prostate cancer by cone beam computed tomography (CBCT)-based dose accumulation and target coverage analysis. Methods Twenty-three patients with localized prostate cancer treated with moderately hypofractionated prostate radiotherapy with simultaneous integrated boost (SIB) between December 2016 and February 2020 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…There are many studies on the robustness evaluation of planning, but at present, there are few studies on the combination of o ine adaptive robustness evaluation and the comparison of planning methods. In a study, Tamihardja [21] conducted evaluation of VMAT robustness in prostate cancer and off-line adaptive evaluation of CBCT. Zhang's study also showed that rectal NTCPs in prostate cancer are highly affected by dose-to-dose variability in CBCT-based soft tissue matching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies on the robustness evaluation of planning, but at present, there are few studies on the combination of o ine adaptive robustness evaluation and the comparison of planning methods. In a study, Tamihardja [21] conducted evaluation of VMAT robustness in prostate cancer and off-line adaptive evaluation of CBCT. Zhang's study also showed that rectal NTCPs in prostate cancer are highly affected by dose-to-dose variability in CBCT-based soft tissue matching.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Buranaporn [4] studied the relationship between dose-received volume and complications of OARs during radiotherapy for bladder cancer, and the applied method was the fusion of CBCT and PCT using DIR for off-line adaptive radiotherapy. Tamihardja's [21] study also used CBCT-based off-line adaptive radiotherapy to assess the difference between actual dose and planned dose in prostate cancer. Wang's [22] study also compared dosimetry differences between daily and weekly CBCT using an MVCBCT-based off-line adaptive approach.…”
Section: Discussionmentioning
confidence: 99%
“…C-RAD systems can quantify setup errors in PMRT for breast cancer treatment. In our traditional radiation therapy, CBCT was a key method for assessing the positioning error (11,26). It enabled us to visualize important anatomical details in the patient's body.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PMRT was used to treat patients who had no tumor tissue in the planning target, and the tumor location was close to the optical body surface, and thus, the impact could be minimized. Implementing adaptive radiotherapy (ART) might solve this problem (11). Additionally, the rotation of the patient in two directions (Pitch and Roll) were not accounted for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation